Respuesta :

Answer:

[tex]a=6[/tex], [tex]b=6\sqrt{2}[/tex], [tex]c=2\sqrt{3}[/tex], and [tex]d=6[/tex]


Step-by-step explanation:


Looking at the left triangle, we can solve for [tex]a[/tex] and [tex]c[/tex].

a:

[tex]a[/tex] is to the opposite side of 60° angle, also we know the hypotenuse, [tex]4\sqrt{3}[/tex]. The ratio that relates opposite with hypotenuse is SINE. Thus we can write:

[tex]sin(A)=\frac{opposite}{hypotenuse}\\sin(60)=\frac{a}{4\sqrt{3}}\\[/tex]

Cross multiplying and solving for [tex]a[/tex]:

[tex]sin(60)=\frac{a}{4\sqrt{3} }\\a=sin(60)*4\sqrt{3}\\a=\frac{\sqrt{3}}{2}*4\sqrt{3}\\a=\frac{12}{2}=6[/tex]

( we know [tex]sin(60)=\frac{\sqrt{3}}{2}[/tex] and also [tex]\sqrt{a}*\sqrt{a}=a[/tex] )


c:

[tex]c[/tex] is to the adjacent side of 60° angle, also we know the hypotenuse, [tex]4\sqrt{3}[/tex]. The ratio that relates adjacent with hypotenuse is COS. Thus we can write:

[tex]cos(A)=\frac{adjacent}{hypotenuse}\\cos(60)=\frac{c}{4\sqrt{3}}[/tex]

Cross multiplying and solving for [tex]c[/tex]:

[tex]cos(60)=\frac{c}{4\sqrt{3}}\\c=cos(60)*4\sqrt{3}\\c=\frac{1}{2}*4\sqrt{3}\\c=2\sqrt{3}[/tex]

( we know [tex]cos(60)=\frac{1}{2}[/tex] )


Looking at the triangle to the right, we can solve for [tex]b[/tex] and [tex]d[/tex].

b:

[tex]a[/tex] is to the opposite side of 45° angle. We have figured out that [tex]a=6[/tex]. Also we know that [tex]b[/tex] is the hypotenuse.The ratio that relates opposite with hypotenuse is SINE. Thus we can write:

[tex]sin(A)=\frac{opposite}{hypotenuse}\\sin(45)=\frac{6}{b}\\b=\frac{6}{sin(45)}\\b=\frac{6}{\frac{1}{\sqrt{2}}}\\b=6*\frac{\sqrt{2}}{1}\\b=6\sqrt{2}[/tex]

( we know [tex]sin(45)=\frac{1}{\sqrt{2}}[/tex] )


d:

To solve for [tex]d[/tex], we can use the pythagorean theorem. Given by:

[tex]a^2+b^2=c^2[/tex]

Where,

  • [tex]a[/tex] and [tex]b[/tex] are two legs of the right triangle, and
  • [tex]c[/tex] is the hypotenuse (side opposite 90 degree angle)

In the triangle on the right, [tex]b[/tex] is the hypotenuse and [tex]a[/tex] and [tex]d[/tex] are the two legs. Using pythagorean theorem and solving for [tex]d[/tex], we get:

[tex]d^2+a^2=b^2\\d^2+(6)^2=(6\sqrt{2})^2\\d^2+36=72\\d^2=72-36\\d^2=36\\d=6[/tex]

( we know that [tex]\sqrt{a}*\sqrt{a}=a[/tex] )


Looking at the answers, 2nd answer choice is right.

ACCESS MORE